Mitotic activity of survivin is regulated by acetylation at K129 - Aljaberi, Aysha M.; Webster, Jamie R.M.; Wheatley, Sally P. (Taylor & Francis, 2015)
Survivin is a cancer-associated protein regulated by multiple factors, including acetylation at K129 within its C-terminal alpha-helical tail. Acetylation of survivin is being pursued as a potential prognostic marker in breast cancer. This modification at K129 may cause nuclear accumulation of survivin in interphase cells; however, whether this affects its essential role during mitosis has not been addressed. We posited whether mimicking acetylation of survivin at K129 alters its activity during mitosis. Fluorescence microscopy and time-lapse imaging showed that, mutating this site to an alanine to act as a constitutive acetyl mimetic, K129A, causes defects in chromosome segregation and cytokinesis. As a non-acetylatable version, K129R, also has difficulty during mitotic exit, we conclude that cyclical acetylation and deacetylation is required for fully functional survivin during mitosis.